Da economia tradicional do bem-estar à importância da equidade em saúde para o desenvolvimento humano - Giacomelli, Giana Silva (2015)
This work aims to incorporate the concept of equity in health and its importance in the discussion of human development within the Economy. Initially, a conversation between health and economy seems impossible, and to achieve this goal, this paper presents a literature course that begins in the traditional theory of welfare and reaches the capabilities approach. By adopting the concept of human development, proposed by the capabilities approach, and connect with the concept of health equity, has a very rich conversation in terms of assessment of the population lives. The capabilities approach adopts a multidimensional concept for human development, for which the life of people is the ultimate goal; health equity refers also to a multidimensional concept that ranges from genetic factors of the individuals to the macroeconomic environment in which they live. Thus, health equity is opening to participate in the economic discussion on human development through the multidimensionality that connects with the capabilities approach. Expand the vision of Economy based on well-being, based on the maximization of the utilities of individuals and development based on income, to a vision that embraces the individual as a whole, consisting of values and social and specific characteristics, it becomes an essential issue when it recognizes that people are the ultimate goal of the progress of countries. The literature survey identified that health equity is inherent to human success, social and economic development of nations, is also a major contemporary concern internationally and is a goal that is strongly linked to human development.